Corrosion inhibition of aluminum in a diesel–biodiesel fuel blend using Thymus vulgaris - Devi A. Nogueron Benitez; Ana K. Larios Galvez; Roy Lopez Sesenes; America M. Ramirez Arteaga; José G. Gonzalez Rodriguez (Green Chemistry Letters and Reviews, 2025)
The use of Thymus vulgaris extract as a green corrosion inhibitor for aluminum in a 20% biodiesel–80% diesel blend has been evaluated using gravimetric and electrochemical techniques, such as linear polarization resistance (LPR), electrochemical impedance spectroscopy (EIS), and electrochemical noise (EN). Additionally, Fourier transform infrared spectroscopy (FTIR) and Gas chromatography-mass spectrometry (GC-MS) analytical techniques were used to characterize both the biodiesel obtained from canola oil and the inhibitor. The results have shown that Thymus vulgaris decreases the Al corrosion rate in the blend due to its physical adsorption onto the metal, according to a Langmuir adsorption isotherm. Its corrosion efficiency increases with an increase in its concentration. The corrosion mechanism was under charge transfer control and was not affected by the addition of the inhibitor or time. The uniform corrosion rateand the localized type of corrosion decrease by the addition of the inhibitor. The main compounds responsible for the anticorrosion properties of Thymus vulgaris include carvacrol and thymol.